Main factors and circumstances, which had promoted for adoption of the African charter on human and peoples’ rights - - Syraba Diallo (RUDN Journal of Law, 2013)
There is shown decisive role, contributed by African jurists in the process of the elaboration and adoption of the African Charter on Human and Peoples’ Rights in this thesis.